South-Western Federal Taxation 2021: Individual Income Taxes, 44th Edition - James C. Young; Annette Nellen; William A. Raabe (Cengage Learning, 2020)
Gain a thorough understanding of today's individual income tax concepts and current tax law with SOUTH-WESTERN FEDERAL TAXATION 2021: INDIVIDUAL INCOME TAXES, 44E. This reader-friendly presentation emphasizes the latest tax law affecting individual taxpayers, including the most recent tax changes and reforms. Complete coverage of the Tax Cuts and Jobs Act of 2017 offers related guidance from the Treasury Department. This book's distinctive ""Framework 1040"" demonstrates both how topics relate to one another and to the Form 1040. Clear examples, frequent summaries and memorable tax scenarios further clarify concepts and help you sharpen critical-thinking, writing and research skills. Learn how taxes impact you personally with the most thorough coverage of individual income taxation today. You can even use this edition to prepare for the C.P.A. exam or Enrolled Agent exam or to begin study for a career in tax accounting, financial reporting or auditing. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.